Impact of Digital Finance on Credit Structure and Risk-Taking in Commercial Banks: An Empirical Analysis - Zhang Zhihui (Ilmu Inovasi Nusantara, 2024)
With the rapid growth of new technologies such as big data, digital technology is increasingly permeating our daily lives. Financial institutions, particularly commercial banks, are also seizing opportunities in the wave of digital financial development to provide better financial services. However, this development in digital finance has affected the credit structure and risk-taking of banks. This study aims to empirically analyze the impact of digital finance development on the credit structure and risk-taking of commercial banks. Additionally, the study seeks to discuss how the combined effects of digital finance and credit structure influence bank risk-taking. Empirical analysis is conducted using financial data from commercial banks over the past decade. The analytical methods include collecting secondary data, statistical data processing, and regression analysis to evaluate the relationships between digital finance development, credit structure, and bank risk-taking. The empirical analysis results show that the development of digital finance has promoted an increase in the scale of bank credit and the ratio of personal loans to credit loans. Integrating digital finance with banks has proven to reduce the risk burden banks bear. Furthermore, as digital finance continues to develop, adjustments in the bank's credit structure also affect the risk burden borne by the banks. Based on these findings, it is recommended that commercial banks continue to adopt digital financial technologies to increase their credit scale and optimize their credit structure. Additionally, banks should consider developing policies that support integrating digital technologies to reduce risk burdens and enhance financial stability. Further research is also suggested to explore the long-term impact of digital finance on the overall financial performance and risk of banks